Unintentional trazodone overdoses in children ≤6 years of age: data from poison center over a period of 16 years. (2nd January 2019) - El Zahran, Tharwat; Morgan, Brent W.; Hon, Stephanie; Herrington, Lloyd; Geller, Robert J.
Abstract: Context: Trazodone is an atypical antidepressant with no established safety in children. Previous case reports showed no complications at doses 50–500 mg in children. Our study objective is to characterize the clinical effects, dose-related toxicity, and establish triage dose for acute trazodone ingestions in children ≤6 years of age. Methods: Cases with acute trazodone ingestions in children ≤6 years of age between 2000 and 2015 were retrospectively reviewed. Data were analyzed for dose (mg/kg), clinical effects, management site, treatment, and outcome. Cases with coingestions, unknown outcome, or unknown dose were excluded. Results: A total of 84 patients (mean age 26.7 months, 35 females, 49 males) were included. Of those, 52 (61.9%) had no clinical effects; 29 (34.5%) had minor effects (vomiting, dizziness, headache); and three (3.6%) had moderate effects (ataxia, slurred speech, priapism). No major effects or deaths were observed. Moderate effects were manifested at doses ≥6.9 mg/kg. Priapism occurred in a 2-year-old child at a dose of 6.9 mg/kg. Sixteen (19%) patients were managed at home and 68 (81%) patients were referred to a HCF. Among those referred to a HCF, three (4.4%) patients had moderate effects with ingested dose ≥6.9 mg/kg. However, 27 (39.7%) patients of those referred to a HCF had an ingested dose <6 mg/kg and none of them manifested symptoms beyond minor effects. All referred patients had uneventful recovery and no sequela. Conclusions: Children should be referred for further evaluation in acute unintentional trazodone ingestions with doses ≥6 mg/kg.